A case report of total breast reconstruction using an inframammary adipofascial flap with an implant. (2016) - Ogawa, Tomoko; Yamakawa, Tomomi
Highlights: Prosthetic-based breast reconstruction can be used in combination with autologous flaps to achieve symmetry. The inframammary adipofascial flap is a new autologous flap for use in combination with prosthetic-based breast reconstruction after nipple-sparing mastectomy (NSM). Total breast reconstruction using the inframammary adipofascial flap with an implant can be performed through the same skin incision on the IMF as NSM. This method is useful for breast reconstruction after NSM for young patients with moderate-ptotic breasts. Abstract: Introduction: Prosthetic-based breast reconstruction can be used in combination with autologous flaps such as a latissimus dorsi (LD) flap or a thoracodorsal artery perforator (TDAP) flap to achieve symmetry. However, the LD and TDAP flaps require a different skin incision from that which is used for the mastectomy. As a new autologous flap for use in combination with prosthetic-based breast reconstruction after nipple-sparing mastectomy (NSM), we used an inframammary adipofascial flap. Presentation of case: The patient was a 27-year-old female with moderate ptotic breasts, who had ductal carcinoma in situ in the lower outer quadrant of her left breast. After NSM through the inframammary fold (IMF) incision, the subcutaneous fat of the intended inframammary area was undermined, and the tongue shaped adipofascial flap was pulled up in the intended area. After inserting a tissue expander under the major pectoral muscle, this adipofascial flap was reflected back to the inferior portion of the breast area. After modeling the breast mound with this flap, the inframammary skin incision was sutured. Eleven months later, the patient underwent surgery to replace the expander with a permanent implant. Eight months after the replacement with an implant, the cosmetic result is good. Discussion: This procedure can be performed through the same skin incision on the IMF as NSM. Total breast reconstruction using the inframammary adipofascial flap with an implant can be an alternative approach to achieving symmetry in some patients. Conclusion: This method is useful for breast reconstruction after NSM for young patients with moderate-ptotic breasts.